EKSISTENSI TRADISI MAKAN BAJAMBA PADA MASYARAKAT KURAI DI KOTA BUKITTINGGI (1984-2021) - Amelia, Stephany; Erniwati, Erniwati (Ensiklopedia of Journal, 2024)
Abstract: This article is a historical study that discusses the Existence of the Bajamba Eating Tradition in the Kurai Community of Bukittinggi City in 1984-2021. This article aims to explain how the survival of the tradition of eating bajamba in the Kurai community after the city of Bukittinggi became a tourist destination city and the strategies carried out by the Kurai community to maintain the tradition of eating bajamba, after the city of Bukittinggi was inhabited by immigrants from various ethnicities. This research uses a historical method consisting of four stages, namely heuristics, source criticism, interpretation, and historiography. The results of this study show that the Kurai community still maintains the tradition of eating bajamba, because eating bajamba is a self-identity for the Kurai community, eating bajamba has existed and has been done since the past, in the implementation of eating bajamba it describes strong customs, closeness, and intimacy in the Kurai community. The community carries out various strategies to maintain the tradition of eating bajamba, by carrying out the tradition of eating bajamba at every Kurai traditional event, holding monthly meetings for the Bundo Kanduang, holding cultural festivals, and adding P5 activities for students to get to know the traditions that exist in their area. Keywords: Existence, Kurai Community, Eating Bajamba